2005
DOI: 10.1007/s00213-005-0182-5
|View full text |Cite
|
Sign up to set email alerts
|

2-MPPA, a selective glutamate carboxypeptidase II inhibitor, attenuates morphine tolerance but not dependence in C57/Bl mice

Abstract: The present findings suggest complex effects of GCP II inhibition on morphine dependence and tolerance and imply a role of mGluR II in the actions of 2-MPPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…2-MPPA has also been administered to human volunteers and was well tolerated with no reports of adverse CNS effects [18]. In previously published studies 2-MPPA, at similar or greater doses to that tested here, have been shown not to cause any effect when given alone to rats or mice [19], [20], [21], [22].…”
Section: Introductionsupporting
confidence: 52%
“…2-MPPA has also been administered to human volunteers and was well tolerated with no reports of adverse CNS effects [18]. In previously published studies 2-MPPA, at similar or greater doses to that tested here, have been shown not to cause any effect when given alone to rats or mice [19], [20], [21], [22].…”
Section: Introductionsupporting
confidence: 52%
“…Reinforcing the conclusion that NAAG mediated these effects via mGluR3, co‐injection of a group II mGluR antagonist, systemically or directly into the nucleus accumbens reversed the effects of the peptide and peptidase inhibitor in these studies. The influence of NAAG on the opiate circuits is somewhat different with peptidase inhibition attenuating tolerance but not dependence in mice (Kozela et al. 2005).…”
Section: Naag Peptidase Inhibition As Drug Abuse Therapymentioning
confidence: 99%
“…Many preclinical and clinical studies have been conducted with the purpose of exploring GCPII regulation strategies for pathological CNS disorders. Inhibition of GCPII has demonstrated beneficial and dose-dependent neuroprotective properties in models of inflammatory and neuropathic pain [152][153][154][155][156][157][158][159][160][161][162][163][164][165][166] brain ischemia [167][168][169][170][171] motor neuron disease [172] spinal cord and traumatic brain injury [173][174][175], peripheral neuropathy [156,161,176,177], epilepsy [178] and drug abuse [179][180][181][182][183][184][185]. Inhibition of GCPII in in vitro and in vivo models of injury cause an increase in extracellular NAAG concentration and a decrease in extracellular glutamate concentration [108].…”
Section: Inhibition Of Gcpii Activity As a Novel Strategy To Treat Comentioning
confidence: 99%